2020
DOI: 10.1016/j.jfluidstructs.2020.102965
|View full text |Cite
|
Sign up to set email alerts
|

Modal analysis of a spinning disk in a dense fluid as a model for high head hydraulic turbines

Abstract: In high head Francis turbines and pump-turbines in particular, Rotor Stator Interaction (RSI) is an unavoidable source of excitation that needs to be predicted accurately. Precise knowledge of turbine dynamic characteristics, notably the variation of the rotor natural frequencies with rotation speed and added mass of the surrounding water, is essential to assess potential resonance and resulting amplification of vibrations. In these machines, the disk-like structures of the runner crown and band as well as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 40 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Louyot proposed an analytical modal analysis method based on an assumed modal approach and potential flow theory and a modal force computational fluid dynamics (CFD) method. Both methods accurately predict intrinsic frequency splitting and intrinsic frequency drift with errors within the experimentally allowed limits [37][38][39][40].…”
Section: Introductionmentioning
confidence: 91%
“…Louyot proposed an analytical modal analysis method based on an assumed modal approach and potential flow theory and a modal force computational fluid dynamics (CFD) method. Both methods accurately predict intrinsic frequency splitting and intrinsic frequency drift with errors within the experimentally allowed limits [37][38][39][40].…”
Section: Introductionmentioning
confidence: 91%
“…In Table 1 some mode shapes of a disk clamped at its center are shown and sorted by the number of nodal diameters (D) and nodal circles (C). As it was studied by many authors [17,26,[28][29][30][31], the vibration mode shapes of a disk have combinations of nodal diameters and nodal circles, which increase their number with the mode order. For convenience, in this work, the mode shapes related to the disk will be called modes "(m, n)" for modes shapes with m nodal diameter and n nodal circles.…”
Section: Modal Characteristics Of a Disk-like Structurementioning
confidence: 99%
“…It was found that while frequencies of the disk decrease when the disk gets close to the rigid wall, the opposite occurs when the disk gets close to the non-rigid wall. Louyot et al [17] made a modal analysis of a spinning disk in a dense fluid as a model for a high-head hydraulic runner. The mode shapes were extracted and, an expression for co-and counter-rotating wave angular frequency was analytically determined.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ND vibration modes evolve from standing mode shapes under non-rotating conditions to traveling mode shapes under rotating conditions. Under non-rotating conditions, the displacements of each point of the disk are either in phase or out of phase, while under rotating conditions the displacements are phase-shifted, resulting in a wave traveling over the disk [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%